Imaging Multispettrale low-cost con filtri interferenziali - Cosentino, Antonio (Archeomatica, 2015)
Multispectral imaging systems are used in art examination in order to map and identify pigments and binders as well as retouches. A monochromatic camera (CCD or InGaAs) is combined with an appropriate wavelength selection system, simple as a set of interferential filters or powerful but expensive as liquid-crystal tunable ï¬lters. A variable number of spectral images of a scene are then acquired and stacked into a reflectance imaging cube to be used to reconstruct reflectance spectra from each of their pixel. This work presents an affordable and simple multispectral imaging system composed of a monochromatic CCD camera and a set of only 12 interferential filters. The system was tested on a mock-up painting realized with traditional and modern pigments and also on a late 1800 authentic oil painting. This system is of particular interest for the cultural heritage sector because of its hardware simplicity, the acquisition speed as well as its lightweight and small dimensions. It must be pointed out that since its small number of filters, this system has limited analytical capacity and it must be used only for the preliminary mapping and identification of the pigments.